Oliveira (Olea europaea L.): armazenamento de pólen, propriedades do estigma e feitos de defensivos agrícolas na microsporogênese - Zambon, Carolina Ruiz (2017)
Brazil is a great importer of olive oil, beginning to emerge for the national production, being an expanding recent business, mainly in the subtropical regions lacking a great deal of technical information such as: data about pollination, pollen viability and stigma receptivity as well as factors which can affect those processes under the particular national environmental conditions. It was intended through this work to test the methodologies which preserve pollen viability along time as well as establish the best timing to intervene in pollen in the stigma during hybridization in cultivar Arbequina, in addition to investigating irregularities occurring during the microsporogenesis of two cultivars: Arbequina and MGS GRAP 541, when submitted to the application of different agricultural defensives during blooming and evaluating whether those abnormalities and viability of pollen grains. During the first experiment, the description of the floral features, storage test of pollen grains under three different conditions were conducted: Environmental temperature (27 °C), refrigerator (8 °C) and freezer (-10 °C) and the last phase, the floral stigma receptivity by the 3% hydrogen peroxide with flowers at pre-anthesis, anthesis and post-anthesis was verified along the day of cultivar Arbequina. As a result, in the description of the floral features, it was found that the olive tree presents diurnal anthesis, with floral opening between 10 and 11 hours, the freezer-stored anthers, had best result, preserving viability for 60 days e the stigmas have proved receptive since pre-anthesis. In the second experiment, inflorescences of two olive cultivars, Arbequina and MGS GRAP541, were submitted to the application of five agricultural defensives: mineral oil, neem oil, dimethoate, deltamethrine and control treatment (water), the flower being fixed in Carnoy and later the percentage of meiotic abnormalities quantified through the protocol for meiotic study by the squash technique and 0.5% propionic carmine staining. During this experiment, the pollen viability was tested by the Alexander staining method and by the in vitro germination method in culture medium specific for olive pollen, the results of the two viability methods being analyzed singly and in joint evaluating their similarity. As a result, the two cultivars presented increase in the percentage of chromosome abnormalities when the agricultural defensives were utilized. In the pollen viability tests, both the methods for the two cultivars presented increased percentage of viable pollen in the control treatment and decreased pollen viability percentage in the presence of the agricultural defensives. The pollen viability method by staining showed the highest means of viable pollens, but, both methods when compared jointly, presented a strongly related positive linear correlation, indicating that both stand for the pollen viability of the treatments.